Environmental eustress modulates β-ARs/CCL2 axis to induce anti-tumor immunity and sensitize immunotherapy against liver cancer in mice - Chaobao Liu (Nature Portfolio, 2021)
The impact of positive environment stimulations (eustress) on cancer biology remains poorly understood. Here the authors show that exposure to an environment enrichment stimulates anti-tumor immunity and reduces tumor growth in preclinical models of liver cancer.